Three-ligament tenodesis for chronic scapholunate injuries: short-term outcomes in 203 patients. (May 2020) - Blackburn, Julia; van der Oest, Mark J. W.; Poelstra, Ralph; Selles, Ruud W.; Chen, Neal C.; Feitz, Reinier
In this cohort study, we report on short-term outcomes of 203 patients (203 wrists) who underwent scapholunate ligament reconstruction using a three-ligament tenodesis technique between December 2013 and December 2017. Patients completed the Patient Rated Wrist Evaluation questionnaire and a visual analogue scale for pain online before surgery and at 3 months and 1 year after surgery. We also measured the range of movement before surgery, in 150 patients 3 months after surgery, and in 90 patients 1 year after surgery. The patients reported clinically significant improvements in both pain and function postoperatively, with continuing improvement at both 3 and 12 months. We conclude that the short-term outcomes of this procedure are generally good in term of patients' function, satisfaction, and pain relief, but about 20% of the operated wrists did not improve. Our data may help patients and surgeons in joint decision-making regarding treatment for chronic scapholunate injuries. Level of evidence: III